2017
DOI: 10.1089/ten.tea.2016.0474
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Gal Inactivated Heart Valve Bioprostheses Exhibit an Anti-Calcification Propensity Similar to Knockout Tissues

Abstract: A novel treatment, called FACTA, is effective to produce biological tissues that are less susceptible to enzymatic and oxidative stress and structural degradation, calcification, and thrombus formation. FACTA-treated tissues display a clear improvement of their biocompatibility that is characterized by an almost complete inactivation of the alpha-Gal epitope. FACTA prevents the xenogeneic tissue antigens from reacting with the host immune system, ensuring an effective shield effect that makes the tissue surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Serum was stored at −80°C until further use for purification 17 . Double knockout (DKO) pigs were obtained by targeting the swine CMAH gene using TALEN 28 on the GGTA12/2 background (obtained from Dr Soulillou through Dr D. H. Sachs, Massachusetts General Hospital, Boston, MA, USA) 29 and by somatic cell nuclear transfer 28,30 . The CKO pigs were generated in Dr C. Galli's laboratory 31 by breeding DKO male founders to WT sows.…”
Section: Methodsmentioning
confidence: 99%
“…Serum was stored at −80°C until further use for purification 17 . Double knockout (DKO) pigs were obtained by targeting the swine CMAH gene using TALEN 28 on the GGTA12/2 background (obtained from Dr Soulillou through Dr D. H. Sachs, Massachusetts General Hospital, Boston, MA, USA) 29 and by somatic cell nuclear transfer 28,30 . The CKO pigs were generated in Dr C. Galli's laboratory 31 by breeding DKO male founders to WT sows.…”
Section: Methodsmentioning
confidence: 99%
“…There is growing interest in using Gal-free animal tissues from Gal-knockout pigs (GTKO) to reduce anti-Gal antibody-associated tissue calcification [18, 21, 22, 37, 38]. While the potential advantage of Gal-free tissue has not been clinically demonstrated, our previous studies have shown that glutaraldehyde-fixed GTKO and standard porcine pericardial tissues have same general morphology, collagen content, and mechanical strength [23].…”
Section: Discussionmentioning
confidence: 99%
“…8 The resulting humoral response leads to activation of the complement system, triggering endothelial cell dysfunction, platelet aggregation, and promotes calcification. 2,[9][10][11] Although the presented study of Veraar and colleagues 5 did not explore any relationship between the degree of immunogenic response and valve durability, other groups were able to show an association of anti-alpha-gal antibodies and premature bioprosthetic valve degeneration. 12 Furthermore, several experimental studies demonstrated a connection between anti-alpha-gal antibodies and the calcification process in valvular bioprosthesis.…”
mentioning
confidence: 88%